A Brief Overview of Deep Learning and Memristor. Issue 1 (April 2021) - Cheng, Guojian; An, Xiaoxin
Abstract: At present, the deep learning has become a main topic in academic and engineering domain. It has been considered to be the general solutions to solve various of classification, clustering, regression and generate tasks in all fields, but it needs higher computing power at the same time. In other words, it needs the new equipment possessing lower power consumption and higher efficiency, which further triggers the development of new hardware and computing technology. A kind of promising solution is an emerging equipment known as memristor, which can be naturally mixed into a feasible computing device to realize neural computing to extend computing power of existing hardware. In this paper, more convenience and practically of using memristor to realize deep neural networks are obtained by summarizing mechanism of deep learning and structure of memristor.